Sustained testosterone suppression: prognostic indicator in advanced hormone sensitive prostate cancer - Ma, Dongsheng; Zhuo, Tao; Huang, Xin; Xi, Jianhong (Frontiers in Endocrinology, 2025)
ObjectiveWe aimed to investigate the relationship between sustained testosterone suppression and clinical outcomes in advanced hormone-sensitive prostate cancer (aHSPC), which integrates longitudinal testosterone with castration duration to predict tumor progression and prognosis.MethodsIn this retrospective study, we analyzed 336 patients with aHSPC from two medical centers who underwent serial testosterone monitoring during androgen deprivation therapy (ADT). The patients were stratified by testosterone suppression sustainability into the testosterone sustained response and testosterone non-sustained response groups. We evaluated the baseline characteristics, time to progression (TTP), and the survival outcomes between groups.ResultsThe cohort demonstrated a median TTP of 18 months and an overall survival of 6.17 years. Patients in the testosterone sustained response group showed significantly better outcomes than those in the testosterone non-sustained response group, with longer median survival (7.58 vs. 3.00 years, p<0.001) and TTP (23.70 ± 14.66 vs. 13.68 ± 7.84 months, p < 0.001). Inverse correlations emerged between minimum testosterone and TTP (r = −0.238, p < 0.001) and between average testosterone and TTP (r = −0.220, p < 0.001). Multivariate analysis identified visceral metastases (adjusted OR = 0.45, 95%CI = 0.21–0.98, p=0.043) and high tumor load (adjusted OR = 0.53, 95%CI = 0.33–0.85, p = 0.008) as negative predictors of testosterone stabilization. The testosterone sustained response group status predicted reduced mortality risk (adjusted HR = 0.605, 95%CI = 0.369–0.990, p = 0.045), while higher minimum testosterone increased the mortality risk (adjusted HR = 1.358, 95%CI = 1.116–1.654, p = 0.002).ConclusionSustained testosterone suppression provides a clinically applicable method for assessing treatment efficacy and predicting prognosis in aHSPC.